Fostering Confidence in Chemistry: How Problem-Based Learning Elevates Self-Efficacy - Simorangkir, Agustina; Rohaeti, Eli (Faculty of Mathematics and Natural Sciences, Universitas Negeri Yogyakarta, 2025)
This article examines the role of Problem-Based Learning (PBL) in fostering self-efficacy among high school students, emphasizing how this pedagogical approach enhances students' self-efficacy in their ability to understand and apply chemistry concepts. By engaging students with real-world problems, PBL promotes active participation and critical thinking, encouraging students to take ownership of their learning. The study investigates how PBL aids students in overcoming challenges traditionally associated with chemistry education by providing hands-on, direct experiences. The research shows a notable difference in students' self-efficacy before and after the implementation of PBL, while no significant change was observed in students' self-efficacy before and after using the scientific approach. This article offers valuable insights for educators seeking to implement PBL in chemistry classrooms as a strategy to enhance student outcomes, foster a deeper understanding of chemistry, and cultivate sustained interest in the subject.